Interface modification material for solid-state lithium metal battery and application method of interface modification material
By combining the polymer matrix with inorganic nanoparticles, forming an interface modified material, and coating the material on the surface of the lithium metal negative electrode, the problem of lithium dendrites in solid-state lithium metal batteries is solved, and the circulation performance and safety of the battery are significantly improved.
Patent Information
- Application Number
- CN202510011526.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-03-28
AI Technical Summary
The interface problem between the lithium metal negative electrode and the solid electrolyte in solid lithium metal batteries leads to the growth of lithium dendrites, increasing interface resistance, and weakening the cycling performance and safety of the battery.
By combining the polymer matrix with inorganic nanoparticles, an interface modified material is formed, and the material is coated on the surface of the lithium metal negative electrode to form an interface modified layer to improve interface stability and mechanical strength and inhibit the growth of lithium dendrites.
Effectively block the direct contact between the lithium metal negative electrode and the solid electrolyte, reduce the interface impedance, improve the cycling performance and safety of the battery, and significantly improve the cycling life and rate performance of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state lithium metal batteries, and in particular to an interface modification material for solid-state lithium metal batteries and an application method thereof. Background Art
[0002] Solid-state lithium metal batteries are widely regarded as a potential solution for the next generation of energy storage technology due to their high energy density, low self-discharge rate and good safety. Compared with traditional liquid electrolyte lithium batteries, solid-state lithium batteries can effectively avoid the safety hazards caused by the flammable and volatile liquid electrolytes, especially in the field of high-power energy storage. However, solid-state lithium metal batteries still face many technical bottlenecks in practical applications, especially the interface problem between the lithium metal negative electrode and the solid electrolyte.
[0003] As an ideal negative electrode material, lithium metal has an extremely high theoretical specific capacity (3860 mAh / g) and the lowest electrochemical potential (-3.04 V vs. standard hydrogen electrode), making it a preferred material for high energy density batteries. However, lithium metal negative electrodes are prone to produce lithium dendrites during the charging and discharging process, especially when in direct contact with solid electrolytes. Due to poor interface contact, the interface resistance increases, resulting in an increase in local current density, which intensifies the growth of lithium dendrites. Once lithium dendrites penetrate the solid electrolyte, they will cause the battery to short circuit and cause safety risks. In addition, due to the poor chemical stability of the solid electrolyte and the lithium metal negative electrode at the interface, side reactions are prone to occur, further weakening the battery's cycle performance and electrochemical stability.
[0004] In the prior art, in order to solve the interface problem between the lithium metal negative electrode and the solid electrolyte, researchers have proposed a variety of interface modification materials and methods. For example, a layer of polymer electrolyte or inorganic protective layer is coated on the surface of the lithium metal negative electrode to improve the chemical stability and ionic conductivity of the interface. However, the existing interface modification materials still have significant deficiencies in electrochemical performance and mechanical strength. Although many polymer-based materials have good flexibility and ionic conductivity, they are prone to degradation during long-term cycles, lack mechanical strength, and cannot stably inhibit the growth of lithium dendrites in the long term. Although inorganic materials have good mechanical strength, they are not flexible enough and are prone to cracks due to volume changes when the battery is repeatedly charged and discharged, resulting in interface failure.
[0005] In addition, the interface problem of solid-state lithium batteries not only affects the cycle life of the battery, but also directly affects its energy density and rate performance. Therefore, developing an interface modification material with excellent interface stability, electrochemical stability, ionic conductivity and mechanical strength, which can effectively inhibit the growth of lithium dendrites and improve the cycle life and safety of solid-state lithium metal batteries, has become one of the current research focuses in the field of solid-state batteries. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a new type of interface modification material, which achieves improved interface stability and mechanical strength by compounding a polymer matrix with inorganic nanoparticles, can effectively inhibit the formation of lithium dendrites during long-term cycles, and significantly improve the performance and safety of solid-state lithium metal batteries.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows: An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that the material comprises the following steps: a. Dissolve 70-95 parts of the polymer matrix in an organic solvent in accordance with the mass fraction, wherein the amount of the solvent is 100%-300% of the mass of the polymer matrix; b. 5-30 parts of inorganic nanoparticles are gradually added to the polymer matrix solution and stirred to form a suspension; c. stirring at a temperature of 40 ° C to 80 ° C for 1-4 hours until a uniform composite material slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 60 ° C to 100 ° C for 1-2 hours to form an interface modification layer.
[0008] Preferably, the polymer matrix is at least one of polyvinylidene fluoride (PVDF), polyethylene glycol (PEG) or polycaprolactone (PCL).
[0009] Preferably, the organic solvent is at least one of N-methylpyrrolidone (NMP), tetrahydrofuran (THF) or chloroform.
[0010] Preferably, the inorganic nanoparticles are at least one of aluminum oxide, silicon dioxide or lithium titanate.
[0011] Preferably, the particle size of the inorganic nanoparticles is 5-50 nm.
[0012] Preferably, the surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal, and the modification steps are: S1: Add 50-70 parts of isocyanate propyl inorganic nanoparticles and 27-54 parts of diaminobenzidine to 200-300 parts of toluene according to mass parts, stir and mix evenly, then add 1-4 parts of stannous octoate, and then stir and react at 70-90°C for 30-60 minutes; S2: Then add 0.006-0.05 parts of difluoro-3-aminopyridine / lithium, control the temperature at 70-90°C, stir and react for 150-190 minutes, and distill to remove toluene to obtain a lithium-philic inorganic nanoparticle.
[0013] Preferably, the preparation method of the isocyanate propyl inorganic nanoparticles is: According to weight, 50-70 parts of inorganic nanoparticles, 2-6 parts of isocyanatepropyl triethoxysilane, 1000-1200 parts of water and 1-3 parts of acetic acid are stirred and reacted at 30-40° C. for 50-100 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
[0014] Preferably, the preparation method of the difluoro-3-aminopyridine / lithium is: By weight, 13-26 parts of difluoro-3-aminopyridine, 7-14 parts of lithium nitrate and 100-200 parts of water are stirred and reacted at 30-40° C. for 50-100 minutes; water is distilled off to obtain difluoro-3-aminopyridine / lithium.
[0015] Preferably, the coating thickness of the composite material slurry is controlled at 5-20 μm.
[0016] Preferably, the method for applying the interface modification material comprises the following steps: a. coating the interface modification material on the surface of the lithium metal negative electrode; b. assembling a solid-state lithium metal battery, contacting the lithium metal anode coated with the interface material with a solid electrolyte, wherein the solid electrolyte is an oxide-based electrolyte or a sulfide-based electrolyte; c. After packaging the battery, perform pre-cycling at room temperature to 60°C. The number of pre-cycling times is 3-10 times, and the charge and discharge current density each time is 0.1-0.5 mA / cm².
[0017] Inorganic nanoparticle modification mechanism: 1) Treatment of inorganic nanoparticles with isocyanatepropyltriethoxysilane: First, the surface of the inorganic nanoparticles is treated with isocyanatepropyltriethoxysilane to obtain isocyanatepropyl inorganic nanoparticles.
[0018] 2) Condensation reaction with diaminobenzidine: Next, the above-mentioned isocyanate propyl inorganic nanoparticles are subjected to a condensation reaction with diaminobenzidine. This step is to combine the diaminobenzidine molecules with the isocyanate propyl functional groups on the surface of the inorganic nanoparticles through a condensation reaction to form lithium-philic inorganic nanoparticles containing benzidine.
[0019] 3) Condensation reaction with difluoro-3-aminopyridine / lithium: Finally, the above-mentioned lithiophilic inorganic nanoparticles containing benzidine are subjected to a condensation reaction with difluoro-3-aminopyridine / lithium. This step is to combine the difluoro-3-aminopyridine / lithium molecules with the benzidine functional groups on the surface of the inorganic nanoparticles through a condensation reaction, and finally obtain lithiophilic inorganic nanoparticles containing benzidine and difluoro-3-aminopyridine / lithium.
[0020] Inorganic nanoparticle modification effects: 1) Enhanced interfacial compatibility with lithium metal: By introducing lithiophilic benzidine and difluoro-3-aminopyridine / lithium structures on the surface of inorganic nanoparticles, the interfacial compatibility between inorganic nanoparticles and lithium metal can be significantly improved. This helps to reduce interfacial resistance and improve the charge and discharge performance of the battery.
[0021] 2) Effectively block the direct contact between the lithium metal negative electrode and the solid electrolyte: The solid lithium metal battery using the modified material of the present invention can effectively block the direct contact between the lithium metal negative electrode and the solid electrolyte, thereby inhibiting the growth of lithium dendrites. This can avoid the occurrence of internal short circuits in the battery and improve the safety of the battery.
[0022] 3) Excellent cycle stability and electrochemical performance: Experiments show that solid-state lithium metal batteries using the modified material of the present invention exhibit excellent cycle stability and electrochemical performance after multiple charge and discharge cycles. This is mainly attributed to the protective effect of the modified material on the lithium metal negative electrode and the good interface compatibility.
[0023] Technical effects of the present invention: The interface modification material of the present invention can effectively block the direct contact between the lithium metal negative electrode and the solid electrolyte, inhibit the growth of lithium dendrites, and avoid internal short circuit of the battery. Experiments show that the solid lithium metal battery using the modification material of the present invention exhibits excellent cycle stability and electrochemical performance after multiple charge and discharge cycles. DETAILED DESCRIPTION
[0024] The essential features and significant effects of the present invention can be reflected from the following embodiments, but they do not limit the present invention in any way, and those skilled in the art can make some non-essential improvements and adjustments based on the content of the present invention. The present invention is further described below through specific implementation methods.
[0025] The test method of the embodiment of the present invention is as follows: The interface modification material is coated on the surface of the lithium metal negative electrode to assemble a solid-state lithium metal battery. The battery is subjected to 200 cycle charge and discharge tests at room temperature, with the current density set at 0.5 mA / cm² and the test voltage range from 2.5V to 4.2V.
[0026] Example 1 An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that the material comprises the following steps: a. Dissolve 70 g of the polymer matrix in an organic solvent, wherein the amount of the solvent is 100% of the mass of the polymer matrix; b. 5g of inorganic nanoparticles were gradually added to the polymer matrix solution and stirred to form a suspension; c at a temperature of 40 ° C, stirring for 4 hours until a uniform composite slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 60 ° C for 2 hours to form an interface modification layer.
[0027] The polymer matrix is polyvinylidene fluoride (PVDF).
[0028] The organic solvent is N-methylpyrrolidone (NMP).
[0029] The inorganic nanoparticles are aluminum oxide.
[0030] The surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal. The modification steps are as follows: S1: 50 g of isocyanate propyl inorganic nanoparticles and 27 g of diaminobenzidine were added to 200 g of toluene, and after stirring and mixing, 1 g of stannous octoate was added, and then stirred and reacted at 70° C. for 60 minutes; S2: Then add 0.006 g of difluoro-3-aminopyridine / lithium, control the temperature to 70° C., stir and react for 190 minutes, and distill toluene to obtain a lithium-philic inorganic nanoparticle.
[0031] The preparation method of the isocyanate propyl inorganic nanoparticles is: 50g of inorganic nanoparticles, 2g of isocyanatepropyltriethoxysilane, 1000g of water and 1g of acetic acid were stirred and reacted at 30°C for 100 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
[0032] The preparation method of the difluoro-3-aminopyridine / lithium is: 13 g of difluoro-3-aminopyridine, 7 g of lithium nitrate and 100 g of water were stirred and reacted at 30° C. for 100 minutes; the water was distilled off to obtain difluoro-3-aminopyridine / lithium.
[0033] The coating thickness of the composite material slurry is controlled at 5 μm.
[0034] The test results in this example: the battery capacity retention rate is 87.6% after 200 cycles, and the interface impedance increases from the initial 31Ω / cm² to 35Ω / cm².
[0035] Example 2 An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that the material comprises the following steps: a. Dissolve 75 g of the polymer matrix in an organic solvent, wherein the amount of the solvent is 200% of the mass of the polymer matrix; b. 15g of inorganic nanoparticles were gradually added to the polymer matrix solution and stirred to form a suspension; c at a temperature of 60 ° C, stirring for 3 hours until a uniform composite slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 80 ° C for 1.5 hours to form an interface modification layer.
[0036] The polymer matrix is polyethylene glycol (PEG).
[0037] The organic solvent is N-methylpyrrolidone (NMP).
[0038] The inorganic nanoparticles are aluminum oxide.
[0039] The surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal. The modification steps are as follows: S1: Add 60 g of isocyanate propyl inorganic nanoparticles and 36 g of diaminobenzidine to 250 g of toluene, stir and mix well, then add 2 g of stannous octoate, and then stir and react at 80° C. for 50 minutes; S2: Then add 0.02 g of difluoro-3-aminopyridine / lithium, control the temperature to 80° C., stir and react for 180 minutes, and distill to remove toluene to obtain a lithium-philic inorganic nanoparticle.
[0040] The preparation method of the isocyanate propyl inorganic nanoparticles is: 60g of inorganic nanoparticles, 5g of isocyanatepropyltriethoxysilane, 1100g of water and 2g of acetic acid were stirred and reacted at 35°C for 75 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
[0041] The preparation method of the difluoro-3-aminopyridine / lithium is: 20 g of difluoro-3-aminopyridine, 10 g of lithium nitrate and 150 g of water were stirred and reacted at 35° C. for 75 minutes; water was distilled off to obtain difluoro-3-aminopyridine / lithium.
[0042] The coating thickness of the composite material slurry is controlled at 10 μm.
[0043] The test results of this example: the battery capacity retention rate is 89.0% after 200 cycles, and the interface impedance increases from the initial 28Ω / cm² to 31Ω / cm².
[0044] Example 3 An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that the material comprises the following steps: a. Dissolve 85 g of the polymer matrix in an organic solvent, wherein the amount of the solvent is 200% of the mass of the polymer matrix; b. 20g of inorganic nanoparticles are gradually added to the polymer matrix solution and stirred to form a suspension; c at a temperature of 60 ° C, stirring for 2 hours until a uniform composite slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 80 ° C for 1.5 hours to form an interface modification layer.
[0045] The polymer matrix is polyethylene glycol (PEG).
[0046] The organic solvent is tetrahydrofuran (THF).
[0047] The inorganic nanoparticles are silicon dioxide.
[0048] The surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal. The modification steps are as follows: S1: Add 60 g of isocyanate propyl inorganic nanoparticles and 48 g of diaminobenzidine to 250 g of toluene, stir and mix well, then add 3 g of stannous octoate, and then stir and react at 80° C. for 50 minutes; S2: Then add 0.04 g of difluoro-3-aminopyridine / lithium, control the temperature to 80° C., stir and react for 180 minutes, and distill toluene to obtain a lithium-philic inorganic nanoparticle.
[0049] The preparation method of the isocyanate propyl inorganic nanoparticles is: 60g of inorganic nanoparticles, 5g of isocyanatepropyltriethoxysilane, 1100g of water and 2g of acetic acid were stirred and reacted at 35°C for 75 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
[0050] The preparation method of the difluoro-3-aminopyridine / lithium is: 19 g of difluoro-3-aminopyridine, 9 g of lithium nitrate and 150 g of water were stirred and reacted at 35° C. for 75 minutes; the water was distilled off to obtain difluoro-3-aminopyridine / lithium.
[0051] The coating thickness of the composite material slurry is controlled at 15 μm.
[0052] The test results in this example: the battery capacity retention rate is 88.7% after 200 cycles, and the interface impedance increases from the initial 28Ω / cm² to 32Ω / cm².
[0053] Example 4 An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that the material comprises the following steps: a. Dissolve 95 g of the polymer matrix in an organic solvent, wherein the amount of the solvent is 300% of the mass of the polymer matrix; b. 30g of inorganic nanoparticles are gradually added to the polymer matrix solution and stirred to form a suspension; c at a temperature of 80 ° C, stirring for 1 hour until a uniform composite slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 100 ° C for 1 hour to form an interface modification layer.
[0054] The polymer matrix is polycaprolactone (PCL).
[0055] The organic solvent is chloroform.
[0056] The inorganic nanoparticles are silicon dioxide.
[0057] The surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal. The modification steps are as follows: S1: Add 70 g of isocyanate propyl inorganic nanoparticles and 54 g of diaminobenzidine to 300 g of toluene, stir and mix well, then add 4 g of stannous octoate, and then stir and react at 90° C. for 30 minutes; S2: Then add 0.05 g of difluoro-3-aminopyridine / lithium, control the temperature to 90° C., stir and react for 150 minutes, and distill to remove toluene to obtain a lithium-philic inorganic nanoparticle.
[0058] The preparation method of the isocyanate propyl inorganic nanoparticles is: 70g of inorganic nanoparticles, 6g of isocyanatepropyltriethoxysilane, 1200g of water and 3g of acetic acid were stirred and reacted at 40°C for 50 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
[0059] The preparation method of the difluoro-3-aminopyridine / lithium is: 26 g of difluoro-3-aminopyridine, 14 g of lithium nitrate and 200 g of water were stirred and reacted at 40° C. for 50 minutes; the water was distilled off to obtain difluoro-3-aminopyridine / lithium.
[0060] The coating thickness of the composite material slurry is controlled at 20 μm.
[0061] The test results of this example: the battery capacity retention rate after 200 cycles is 90.1%, and the interface impedance increases from the initial 26Ω / cm² to 29Ω / cm².
[0062] Comparative Example 1 The preparation of the interface modified material is basically the same as that of Example 1, except that the inorganic nanoparticles in step b are not subjected to lithium-philic modification treatment.
[0063] The test results in this example: the battery capacity retention rate is 77.5% after 200 cycles, and the interface impedance increases from the initial 42Ω / cm² to 53 Ω / cm².
[0064] Comparative Example 2 The preparation of the interface modification material is basically the same as that of Example 1, except that no difluoro-3-aminopyridine / lithium is added during the lithium-philic modification of the inorganic nanoparticles in step b.
[0065] The test results in this example: the battery capacity retention rate is 83.5% after 200 cycles, and the interface impedance increases from the initial 37Ω / cm² to 44Ω / cm².
[0066] Comparative Example 3 The preparation of the interface modification material is basically the same as that of Example 1, except that no isocyanatepropyltriethoxysilane is added during the lithium-philic modification of the inorganic nanoparticles in step b.
[0067] The test results of this example: the battery capacity retention rate is 80.2% after 200 cycles, and the interface impedance increases from the initial 40Ω / cm² to 49Ω / cm².
[0068] The interface modification materials of the present invention have good interface stability in solid-state lithium metal batteries, can effectively inhibit the growth of lithium dendrites, reduce interface impedance, and improve the cycle performance and safety of the battery. These materials not only have high electrochemical stability, but also can maintain structural integrity during long-term use, significantly improving the cycle life and rate performance of the battery.
[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An interface modification material for solid-state lithium metal batteries and an application method thereof, characterized in that: The following steps are involved: a. Dissolve 70-95 parts of the polymer matrix in an organic solvent in accordance with the mass fraction, wherein the amount of the solvent is 100%-300% of the mass of the polymer matrix; b. 5-30 parts of inorganic nanoparticles are gradually added to the polymer matrix solution and stirred to form a suspension; c. stirring at a temperature of 40 ° C to 80 ° C for 1-4 hours until a uniform composite material slurry is formed; d. The composite material slurry is evenly coated on the surface of the lithium metal negative electrode and dried at 60 ° C to 100 ° C for 1-2 hours to form an interface modification layer.
2. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 1, characterized in that: The polymer matrix is at least one of polyvinylidene fluoride, polyethylene glycol or polycaprolactone.
3. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 1, characterized in that: The organic solvent is at least one of N-methylpyrrolidone, tetrahydrofuran or chloroform.
4. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 1, characterized in that: The inorganic nanoparticles are at least one of aluminum oxide, silicon dioxide or lithium titanate.
5. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 4, characterized in that: The particle size of the inorganic nanoparticles is 5-50 nm.
6. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 4, characterized in that: The surface of the inorganic nanoparticles is treated with lithium-philic modification to enhance the interfacial compatibility with lithium metal. The modification steps are as follows: S1: Add 50-70 parts of isocyanate propyl inorganic nanoparticles and 27-54 parts of diaminobenzidine to 200-300 parts of toluene according to mass parts, stir and mix evenly, then add 1-4 parts of stannous octoate, and then stir and react at 70-90°C for 30-60 minutes; S2: Then add 0.006-0.05 parts of difluoro-3-aminopyridine / lithium, control the temperature at 70-90°C, stir and react for 150-190 minutes, and distill to remove toluene to obtain a lithium-philic inorganic nanoparticle.
7. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 6, characterized in that: The preparation method of the isocyanate propyl inorganic nanoparticles is: According to weight, 50-70 parts of inorganic nanoparticles, 2-6 parts of isocyanatepropyl triethoxysilane, 1000-1200 parts of water and 1-3 parts of acetic acid are stirred and reacted at 30-40° C. for 50-100 minutes; filtered and dried to obtain isocyanatepropyl inorganic nanoparticles.
8. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 6, characterized in that: The preparation method of the difluoro-3-aminopyridine / lithium is: By weight, 13-26 parts of difluoro-3-aminopyridine, 7-14 parts of lithium nitrate and 100-200 parts of water are stirred and reacted at 30-40° C. for 50-100 minutes; water is distilled off to obtain difluoro-3-aminopyridine / lithium.
9. The interface modification material for solid-state lithium metal batteries and the application method thereof according to claim 1, characterized in that: The coating thickness of the composite material slurry is controlled at 5-20 μm.
10. An interface modification material for solid-state lithium metal batteries and an application method thereof according to claims 1-9, characterized in that: The interface modification material application method comprises the following steps: a. coating the interface modification material on the surface of the lithium metal negative electrode; b. assembling a solid-state lithium metal battery, contacting the lithium metal anode coated with the interface material with a solid electrolyte, wherein the solid electrolyte is an oxide-based electrolyte or a sulfide-based electrolyte; c. After packaging the battery, perform pre-cycling at room temperature to 60°C. The number of pre-cycling times is 3-10 times, and the charge and discharge current density each time is 0.1-0.5 mA / cm².